Histamine involvement in visual development and adaptation. - Bessinis, Dimitrios P; Dalla, Christina; Daifoti, Zeta Papadopoulou; Tiligada, Ekaterini (Invest Ophthalmol Vis Sci, 2012)
PURPOSE: This study evaluated the level of histamine in the interaction between the environment and the visual system during lifespan development, exploring potential sex differences. METHODS: Male and female Wistar rats, reared in standard laboratory or enriched-environment cages from birth to prepuberty or adulthood, were sacrificed during the critical period for visual development at postnatal day (P) 25 (P25) or in adulthood at P90. Additionally, animals born in standard conditions were exposed to an enriched environment at P90 and sacrificed at P150. The optic chiasm and the visual cortex were dissected out and tissue histamine was quantified fluorophotometrically. Statistical analyses were performed by ANOVA. RESULTS: Histamine levels in the optic chiasm were higher in male than in female rats at all ages. Comparable sex differences in the visual cortex were observed only during prepuberty. Basal histamine content in the optic chiasm was higher in prepuberty and decreased in adulthood in a sex-independent manner. Exposure to an enriched environment decreased optic chiasm histamine levels in both sexes and resulted in no sex difference in the cortical histamine levels at any age. Increased amine levels were detected in the optic chiasm of female rats exposed to an enriched environment during adulthood. CONCLUSIONS: This study presents first evidence associating central histamine levels with the visual system development and environmental adaptation, thus providing the lead for the investigation of the hitherto elusive role of histamine in the regulation of visual processes. Furthermore, the findings challenge the impact of laboratory animal raising environments in developmental and behavioral studies.
Keywords: Adaptation, Physiological; Animals; Female; Histamine; Male; Models, Neurological; Optic Chiasm; Rats; Rats, Wistar; Visual Cortex